Analyzing the Impact of Foreign Remittances upon Poverty: A Case of Uzbekistan from Central Asia. - Kayani, Farrukh Nawaz (International Journal of Economics and Financial Issues, 2022)
Remittances have always played a central role in strengthening the economies of low-income and middle-income developing countries. The remittances have also provided a phenomenal support to the economy of Uzbekistan, which is the third leading recipient country of foreign remittances in the Central Asian region after Kyrgzstan and Tajikistan. There is a strong need to investigate the impact of foreign remittances upon poverty reduction in case of Uzbekistan. This study has empirically investigated the impact of remittances on poverty in Uzbekistan by taking the variables like remittances, poverty size, capital formation, per capita GDP, savings and unemployment for the period of 2008-2019. Ordinary Least Square Regression was applied, and the results show an insignificant relationship between foreign remittances and poverty reduction. The reason could be that remittances in Uzbekistan are not pro-poor as mostly the workers from the rich families migrate to Russia. Furthermore most of the migrant workers prefer to settle down in Russia along with their families.